2018
DOI: 10.1038/s41372-018-0207-7
|View full text |Cite
|
Sign up to set email alerts
|

Implementation of the sepsis risk score for chorioamnionitis-exposed newborns

Abstract: Algorithm implementation decreased antibiotic and resource utilization without missing cases of EOS.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
23
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 18 publications
(26 citation statements)
references
References 26 publications
3
23
0
Order By: Relevance
“…The presented study is the first report from the Kingdom of Saudi Arabia on implementing the EOS calculator among newborns. Our study's results were comparable with other studies evaluating the infection calculator's validity [ 16 , 17 ]. By applying the EOS calculator in well-appearing and equivocal groups, we found that antibiotic usage could significantly decrease from 100.0% to 0 (P=0.0009) and from 100.0% to 33.3% (P=0.0035), respectively.…”
Section: Discussionsupporting
confidence: 89%
“…The presented study is the first report from the Kingdom of Saudi Arabia on implementing the EOS calculator among newborns. Our study's results were comparable with other studies evaluating the infection calculator's validity [ 16 , 17 ]. By applying the EOS calculator in well-appearing and equivocal groups, we found that antibiotic usage could significantly decrease from 100.0% to 0 (P=0.0009) and from 100.0% to 33.3% (P=0.0035), respectively.…”
Section: Discussionsupporting
confidence: 89%
“…26,27,29 Ten of 13 studies were performed in the United States. 15,27,[29][30][31][33][34][35][36][37] The 13 included studies involved a total of 175 752 newborns. Of these, 172 385 were included in studies comparing cohorts before (66 949) and after (105 436) EOS calculator implementation, and 3367 were included in studies performing hypothetical database analysis.…”
Section: Characteristics and Participants Of Included Studiesmentioning
confidence: 99%
“…Studies evaluating the EOS calculator have provided evidence of secondary benefits associated with EOS calculator implementation, such as reductions in the number of laboratory tests and blood cultures taken [2] and the rate of admissions to neonatal intensive care [5,6]. These findings, together with the reduction in empiric antibiotic treatment, suggest that the use of the EOS calculator may lead to a reduction in overall healthcare utilization and associated healthcare costs.…”
Section: Introductionmentioning
confidence: 99%